Differential Exhumation Across the Longriba Fault System: Implications for the Eastern Tibetan Plateau. Issue 2 (26th February 2018) - Ansberque, Claire; Godard, Vincent; Olivetti, Valerio; Bellier, Olivier; de Sigoyer, Julia; Bernet, Matthias; Stübner, Konstanze; Tan, Xibin; Xu, Xiwei; Ehlers, Todd A.
Abstract: The deformation processes at work across the eastern margin of the Tibetan Plateau remain controversial. The interpretation of its tectonic history is often polarized between two deformation models: ductile flow in the lower crust and shortening and crustal thickening accommodated by brittle structures in the upper crust. Many geological investigations on this plateau margin focused on the Longmen Shan, at the western edge of the Sichuan Basin. However, the Longriba fault system (LFS) located 200 km northwest and parallel to the Longmen Shan structures provides an opportunity to understand the role of hinterland faults in eastern Tibet geodynamics. For this reason, we investigate the exhumation history of rocks across the LFS using (U‐Th)/He and fission track ages from apatite and zircon. Results show a significant contrast in cooling histories across the Maoergai fault, the southernmost fault of the LFS. South of the Maoergai fault, the bedrock records a rapid increase in exhumation rate since ~10–15 Ma. In contrast, the area north of the fault has experienced steady cooling since ~25–35 Ma. We attribute this cooling contrast to ~2 km of differential rock uplift across the Maoergai fault, providing the first evidence of activity of the LFS in the Late Cenozoic. Our results indicate that deformation of the eastern Tibetan margin has been partitioned into the LFS and the Longmen Shan over an ~200 km wide block, which should be incorporated in future studies on the region's deformation, and in both above‐mentioned deformation models. Key Points: Slow cooling bedrock is recorded at ~25–35 Ma north of the LFS, while a rapid cooling bedrock occurs at ~10–15 Ma south of the LFS The differential exhumation across the LFS is attributed to ~2 km differential rock uplift across the Maoergai fault The exhumation of the eastern Tibetan margin is partitioned onto distinct faults over a ~200 km wide block: the LFS and Longmen Shan faults